Compilation of registered clinical trials for the treatment of COVID-19 infection - Kaur, Sukhpreet; Singh, Harminder; Kaur, Kamalpreet (International Journal of Basic & Clinical Pharmacology, 2021)
The Wuhan city, the capital of Hubei province in China became the focal point for origin of virulent disease which later named as COVID-19. This paper aims to analyze the on-going clinical trials for drugs/interventions used for treatment of COVID-19 infection in open domain. The data on ongoing clinical trials on COVID-19 was retrieved from database clinicaltrials.gov. The data extracted includes national clinical trial registry number, title of study, recruitment status, results availability, intervention, outcome measure, sponsorship, study types, study design, start and completion dates, and location. All the extracted data was analyzed. As on 10th August 2020, a total of 2935 trials were registered in different countries. Of which 1115 trials are being conducted in Europe and 640 in United States of America (USA). Majority of COVID-19 clinical trials (95%) were enrolling all age groups including children and older adults. Similarly, majority of trials were including both genders (97%). Among all these clinical trials ongoing on COVID-19, 1645 were interventional, 1266 were observational studies. In interventional study 876 trials used drug intervention. Among all these trials 390 different drug interventions are being tried. Among these hydroxychloroquine, antiretrovirals and angiotensin converting enzyme (ACE) inhibitors were top three drug groups. The conduct of clinical trials in time of pandemic have so many tenacious issues that need to be addressed. It is very important to utilize the resources efficiently such as following a standard protocol then one can easily pool the data of various trials conducted at various places. Given the smaller sample sizes, long completion period, high risk of bias and imprecise information, it will take quite a long time to obtain high quality clinical evidence for the treatment of COVID-19 infection.